2022
DOI: 10.1017/s0033291721005493
|View full text |Cite
|
Sign up to set email alerts
|

The effects of acute tryptophan depletion on instrumental reward learning in anorexia nervosa – an fMRI study

Abstract: Background The serotonin (5-HT) hypothesis of anorexia nervosa (AN) posits that individuals predisposed toward or recovered from AN (recAN) have a central nervous hyperserotonergic state and therefore restrict food intake as a means to reduce 5-HT availability (via diminished tryptophan-derived precursor supply) and alleviate associated negative mood states. Importantly, the 5-HT system has also been generally implicated in reward processing, which has also been shown to be altered in AN. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…Unlike other serotonergic medications requiring repeated administrations, a single dose of psilocybin may lead to rapid and enduring synaptic adaptations that have the potential to improve AN symptoms 10 . However, the role of 5-HT dysfunction in AN and related affective states associated with restriction remains poorly understood with mixed findings 11 , 12 .…”
Section: Mainmentioning
confidence: 99%
“…Unlike other serotonergic medications requiring repeated administrations, a single dose of psilocybin may lead to rapid and enduring synaptic adaptations that have the potential to improve AN symptoms 10 . However, the role of 5-HT dysfunction in AN and related affective states associated with restriction remains poorly understood with mixed findings 11 , 12 .…”
Section: Mainmentioning
confidence: 99%
“…The same group reported that, despite the reduction of TRP/LNAA ratio, there was no difference in anxiety and mood between recovered AN ( n = 22) and healthy controls ( n = 25) exposed to TRP depletion [ 91 ]. Finally, based on functional magnetic resonance imaging, acute TRP depletion was shown to normalize the reward-related neural responses in recovered AN ( n = 22) compared to controls ( n = 25) [ 92 ].…”
Section: Dietary Interventionsmentioning
confidence: 99%